An Introduction to Islamic Law - Schacht, Joseph (OXFORD UNIVERSITY PRESS, 1964)
This book presents a broad account of the present knowledge of the history and outlines the system of Islamic law. Showing that Islamic law is the key to understanding the essence of one of the great world religions, this book explores how it still influences the laws of contemporary Islamic states, and is in itself a remarkable manifestation of legal thought.